2015
DOI: 10.1002/ar.23285
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Human Bone Microstructure in MedievalEngland: Comparisons between Two Socio‐Economic Groups

Abstract: Understanding the links between bone microstructure and human lifestyle is critical for clinical and anthropological research into skeletal growth and adaptation. The present study is the first to report correspondence between socio-economic status and variation in bone microstructure in ancient humans. Products of femoral cortical remodeling were assessed using histological methods in a large human medieval sample (N 5 450) which represented two distinct socio-economic groups. Osteonal parameters were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 126 publications
(164 reference statements)
5
89
0
1
Order By: Relevance
“…There is substantial inter‐individual variation in Ot.Dn values from this region (younger adults range between 394.87 and 1307.69; middle aged adults between 305.77 and 1255.13). Some of this variation in Ot.Dn probably reflects differences in femoral mechanical loading between individuals, as some adults in our sample would have been employed in the physically demanding occupations that were typical of lower socio‐economic lifestyles in medieval Canterbury (Miszkiewicz & Mahoney, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial inter‐individual variation in Ot.Dn values from this region (younger adults range between 394.87 and 1307.69; middle aged adults between 305.77 and 1255.13). Some of this variation in Ot.Dn probably reflects differences in femoral mechanical loading between individuals, as some adults in our sample would have been employed in the physically demanding occupations that were typical of lower socio‐economic lifestyles in medieval Canterbury (Miszkiewicz & Mahoney, ).…”
Section: Discussionmentioning
confidence: 99%
“…Femoral length data were previously included in robusticity index calculations as part of another project (Miszkiewicz & Mahoney, ), but correlations between Ot.Dn and stature/femur length are examined here for the first time. The maximum length of each femur was measured by placing it flat on an osteometric board, in its anatomical position, with the posterior femoral aspect facing down.…”
Section: Methodsmentioning
confidence: 99%
“…On.Ar and On.Dm [40][41][42][43] because they can provide an indication of the type of loading on a bone [44][45][46]. Experimental studies have revealed that osteon size, on average, is inversely related to biomechanical strain [47][48][49].…”
Section: Bone Histomorphometrymentioning
confidence: 99%
“…compound microscope with an Olympus DP25 microscope camera [41,67]. For each rib thinsection the entire cortex was imaged at 20x magnification with a 10x objective and stitched together into a montage using CELL® Live Biology Imaging software (figure 2a).…”
Section: Bone Histologymentioning
confidence: 99%
“…All sampling followed appropriate codes of ethics for research conducted on human skeletons [29]. These skeletons have previously been incorporated into a study that examined histomorphometric variables in adult femoral cortical bone [30].…”
Section: Samplementioning
confidence: 99%